PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS, DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DI BALAI BESAR PEMERINTAHAN DESA DI MALANG - Bili, Sherin; Graha, Andi Nu; Puspitosari Suharso, Arien Anjar (ITB AAS Indonesia Surakarta, 2024)
Employee performance plays a critical role in improving organizational progress. Various factors such as career advancement, work ethics, and democratic leadership approach impact the enhancement of employee performance. The purpose of this study was to determine, in part simultaneously, how democratic leadership style, work discipline, and career development affect employee performance in the Village Government Centre in Malang. This research makes use of quantitative methods. Using the saturation sampling technique, 35 employees of the Center for Village Government in Malang were chosen to comprise the research sample, which included the whole population. techniques for use a questionnaire to collect data. The data analysis method utilized is multiple linear regression, and SPSS 26 is the program used to do this. The study's conclusions show that career development, work discipline, and a democratic leadership style all have a substantial influence on worker performance at the Village Government Centre in Malang. A partial body of research indicates that employee productivity is significantly impacted by work discipline, career development, and democratic leadership approaches. These results highlight the potential benefits of career development, workplace discipline, and democratic leadership styles for improving worker performance. Keywords : Democratic Leadership Style, Work Discipline, Career Development, Performance Employee